Kinetic and isotherm studies on the adsorption–desorption of technical-grade endosulfan in loamy soils under Theobroma cacao L cultivation, Southwestern Nigeria. Issue 2 (23rd December 2022) - Vaikosen, Edebi N.; Davidson, Christine M.; Olu-Owolabi, Bamidele I.; Gibson, Lorraine T.; Agunbiade, Foluso O.; Kashimawo, Adesegun J.; Adebowale, Kayode O.
Abstract : Fate of technical endosulfan in T. cacao L farm soils was studied using the OECD batch model. Rate constants for α- and β-isomers ranged from 6.91 × 10 −3 to 2.85 × 10 −4 min −1 . Pesticide was leachable. TOM/clay could be used as mitigants for its mobility. Abstract : The fate of pesticides in soils is dependent on the adsorption–desorption kinetics, isotherms and soil types. Interactions of technical-grade endosulfan with top soils (top 0–15 cm) from CRIN, Igba and Sore Bale Theobroma cacao L farms in Southwestern Nigeria were studied using the OECD batch isotherm method. The soils were predominately basic (pH 7.1–8.33), while the orders of the total organic carbon (1.32–2.03%) and clay content (10.92–19.11%) were CRIN > Igba > Sore Bale and Igba > CRIN > Sore Bale, respectively. The adsorption of endosulfan was bi-continuous: initially rapid, followed by a slow process, with pseudo-equilibria and plateaus formed between 120 and 240 min. Endosulfan adsorption by soils was due to their greater affinity for organic matter than clay. The adsorption rates fitted better into a pseudo-second-order model (PSOM) than a pseudo-first-order model (PFOM), with the adsorption ( k ads ) and desorption ( k des ) rate constants for both isomers ranging from 7.60 × 10 −3 to 11.52 × 10 −3 min −1 and 1.39 × 10 −3 to 3.42 × 10 −3 min −1, respectively ( i.e. k ads > k des ), while k des (β-isomer) > k des (α-isomer) for PFOM, but k 2_ads < k 2_des for the two isomers in PSOM. Additionally, α-endosulfan was adsorptive, with the β-isomer more prone to leaching; both isomers were moderately leachable according to their FAO mobility rankings. The adsorption model did not fit well into a Langmuir isotherm ( R 2 ≤ 0.948); however, the desorption model did ( R 2 ≥ 0.991). Freundlich isotherm plots fitted better ( R 2 ≥ 0.992) and exhibited non-linear curves of types L and S for the adsorption and desorption processes, respectively. The adsorption/desorption coefficients ( K fads and K fdes ) and strengths of adsorption/desorption (1/ n ads and 1/ n des ) for both isomers were from 1.33 ± 0.10 to 4.81 ± 0.18 μg 1−1/ n (mL) 1/ n g −1 and 0.503 to 1.402, respectively, in all soils, with K fads < K fdes and 1/ n ads < 1/ n des . Positive hysteresis was observed. CRIN exhibited the highest hysteresis index. The K fom values were ≤127.14 ± 6.23 mL g −1, while the values of the standard free energy were Δ G 0 = −5.11 to −14.05 kJ mol −1 K −1, depicting a spontaneous physisorption process, driven by van der Waals forces, among others. Endosulfan could easily be leached and contaminate the surface and groundwater owing to its faster PSOM desorption rate constant, but TOM and clay could be used as mitigants to reduce its mobility in soils as they have significant affinity for the pesticide.